Kombinasi Infrared dan William Flexion Exercise Efektif Menurunkan Nyeri dan Meningkakan Fleksibilitas Otot Pada Kasus Low Back Pain Miogenik - Nurul Halimah; Angria Pradita; Mokhtar Jamil (FORIKES, 2022)
Low back pain is a contemporary neurophysiological pain that distorts pain perception and causes limitation of physical activity. So research is needed which aims to determine the effect of a combination of infrared and William flexion exercises on changes in pain intensity and muscle flexibility. The research design was one group pretest–posttest, involving 40 patients with low back pain who were selected using a purposive sampling technique. The intervention given was physiotherapy in the form of infrared combined with William flexion exercises for a month. Pain level was measured using a visual analogue scale (VAS) and Modified Schober Test (MST) which were measured before and after 8 times of physiotherapy. The hypothesis was tested with the Wilcoxon test. The median VAS value before the intervention was 6.00 and after the intervention was 2.00 with a p value of 0.00. The median MST value pre-intervention was 18.00 and post-intervention was 25.00 with a p-value of 0.00. It was concluded that the combination of infrared and william flexion exercise can reduce pain and increase muscle flexibility in cases of myogenic low back pain.Keywords: low back pain; infrared; William flexion exercise ABSTRAK Low back pain merupakan nyeri neurofisiologis kontemporer yang mendistorsi persepsi nyeri dan menyebabkan keterbatasn aktivitas fisik. Maka diperlukan penelitian yang bertujuan untuk mengetahui pengaruh kombinasi infrared dan latihan William flexion terhadap perubahan intensitas nyeri dan fleksibilitas otot. Rancangan penelitian ini one group pretest–posttest, yang melibatkan 40 penderita low back pain yang dipilih dengan teknik purposive sampling. Intervensi yang diberikan adalah fisioterapi berupa infrared yang dikombinasikan dengan latihan William flexion selama sebulan. Tingkat nyeri diukur menggunakan visual analogue scale (VAS) dan Modified Schober Test (MST) yang diukur sebelum dan setelah 8 kali fisioterapi. Hipotesis diuji dengan Wilcoxon test. Nilai VAS median pra intervensi adalah 6,00 dan pasca intervensi adalah 2,00 dengan nilai p 0,00. Nilai median MST pra intervensi adalah 18,00 dan pasca intervensi adalah 25,00 dengan nilai p 0,00. Disimpulkan bahwa kombinasi infrared dan william flexion exercise dapat menurunkan nyeri dan meningkatkan fleksibilitas otot pada kasus low back pain miogenik.Kata kunci: low back pain; infrared; William flexion exercise